2009
DOI: 10.22358/jafs/66422/2009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fat-coated organic acid salts and a feed enzyme on growth performance, nutrient utilization, microflora activity, and morphology of the small intestine in broiler chickens

Abstract: The efficacy of two fat-coated organic acid preparations added alone or in combination with a commercial feed enzyme to a wheat-and soyabean meal-based broiler diet was investigated. Fat-coated sodium butyrate (SB) and blend G composed of fumaric acid, calcium formate, calcium propionate and potassium sorbite were used. Each preparation was added at 1 g/kg diets cold pelleted. Two hundred 40-day-old Cobb broiler females were allocated to 6 groups, 40 in each, and fed experimental diets from the first day of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 12 publications
8
43
0
2
Order By: Relevance
“…Similar comparable caecal pH was also recorded when 0.03 % fat coated SB (Smulikowska et al, 2009) and 0.1 % SB together with essential oil (Cerisuelo et al, 2014) were used in broiler ration.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 76%
See 1 more Smart Citation
“…Similar comparable caecal pH was also recorded when 0.03 % fat coated SB (Smulikowska et al, 2009) and 0.1 % SB together with essential oil (Cerisuelo et al, 2014) were used in broiler ration.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 76%
“…Further, an increase in the villus height and villus height to crypt depth ratio are directly correlated with increased epithelial cell turnover (Fan et al, 1997) and an indicator of activated intestinal villi function (Langhout et al, 1999;Shamoto and Yamauchi, 2000) and it also stimulates intestinal blood flow. In addition, butyrate of stimulates cell growth and differentiation of normal cells and apoptosis (early cell death) of tumour cells which represents'butyrate paradox' (Canani et al, 2011).Previous studies showed increased jejunum villi height (Adil et al, 2010;Jerzsele et al, 2012;Chamba et al, 2014), villi height to crypt depth ratio (Hu and Guo, 2007;Shahir et al, 2013) and comparable crypt depth (Hu and Guo, 2007;Adil et al, 2010;Smulikowska et al, 2009;Chamba et al, 2014;Sayrafi et al, 2011;Antongiovanni et al, 2007) by supplementation of different forms of butyric acid. Lakshmi and Sunder (2015) 0.25 Liver weight + Aghazadeh and Yazdi (2012) It is clear from the Table 4 that inclusion of BA in broiler diet improves the weight of carcass indicating anabolic effect in broiler chicken.…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…Adil et al (2010) reported that dietary butyric acid (3% application rate) significantly increased the villus height in the duodenum and jejunum only. Similarly, many researchers have described the beneficial effect of dietary sodium butyrate on villi height and crypt depth in broilers at different phases of their growth (Antongiovanni et al, 2007;Mallo et al, 2012;Panda et al, 2009;Sayrafi et al, 2011;Smulikowska et al, 2009). On the contrary, some researchers did not find any effect of dietary sodium butyrate on villi height and crypt depth (Leeson et al, 2005).…”
Section: Gut Morphologymentioning
confidence: 99%
“…In comparison with ruminants, proteolytic activity in the rabbit caecum is relatively higher (Gidenne, 1997). The lower recorded ammonia concentration in T1 and T3 group could be attributed to either increased nitrogen retention by enterocytes and colonocytes in these groups which may be connected with greater epithelial cell proliferation in gastrointestinal tract as suggested by Smulikowska et al (2009) or better ammonia utilization in liver for protein production, this seems true since albumen concentrations were increased in T1 and T3 groups. The decreased in caecal pH, the decreased in ammonia-N concentration and the higher VFA concentration suggest high fermentation activity, caecal microbial synthesis, gut health and high nitrogen retention.…”
Section: T T T Wwwccsenetorg/jasmentioning
confidence: 86%
“…This observation may be due to an increase in TVFA concentration reported in former groups. These short-chain carboxylic acids in the gastrointestinal tract of non-ruminants reflect the amount consumed and the rate of intraluminal production by anaerobic microorganisms from fermentable substrate (Smulikowska et al, 2009). These acids have a number of important regulatory functions related to gastrointestinal functionality, among others mucosal development, proliferation, differentiation, maturation and apoptosis of enterocytes and colonocytes (Mroz et al, 2006).…”
Section: T T T Wwwccsenetorg/jasmentioning
confidence: 99%